Tekstens rum og scenens litteratur: Et personligt essay om at iscenesætte litteratur - Boyding, Rebekka (Passage - Tidsskrift for litteratur og kritik, 2025)
The Scene in Literature and Literature for the Scene: A Personal Essay on Adapting Literature for the Stage In this text, readers are taken on a personal journey from a first encounter with Danish author Cecilie Lind’s publications to a staging of Lind’s novel Girlbeast at Danish theatre Sort/Hvid in 2023 with re-staging in 2025. By diving into the process of adapting and staging the novel, the essay examines what this process can teach us about literature, performing arts and the interplay between the two with the argument that literature in general has a spatial and affective potential not unlike any live and living artform.